Polymeric heptazine imide by O doping and constructing van der Waals heterostructures for photocatalytic water splitting: a theoretical perspective from transition dipole moment analyses. Issue 18 (13th March 2020) - Zhang, Xirui; Yu, Chao; Guan, Jintong; Jiang, Shicheng; Wang, Yunhui; Deng, Kaiming; Meng, Zhaoshun; Lu, Ruifeng
Abstract : Transition dipole moment is suggested as a bridge between band structure and optical absorption in semiconductor photocatalysts and as referential descriptor for interlayer photoexcitation in layered heterostructures. Abstract : Semiconductor-based photocatalysts have received extensive attention for their promising capacity in confronting global energy and environmental issues. In photocatalysis, a large band gap with suitable edge-position is necessary to warrant enough driving force for reaction, whereas a much smaller band gap is needed for visible-light response and high solar energy conversion efficiency. This paradox hinders the development of photocatalysts. Via state-of-the-art first-principles calculations, we find that the transition dipole moments (TDMs) are changed significantly in O-doped partly polymerized g-C3 N4, i.e., OH-terminated polymeric heptazine imide (PHI-OH), and concomitantly, an enhancement of visible-light absorption is achieved; meanwhile a large enough band gap can provide a powerful driving force in the photocatalytic watersplitting reaction. Furthermore, by using TDM analysis of the PHI-OH/BC3 N heterostructure, direct light excited transition between two building layers can be confirmed, suggesting it as a candidate catalyst for hydrogen evolution. From TDM analysis of the PHI-OH/BCN heterostructure, we also verify a Z-scheme process, which involves simultaneous photoexcitations with strong reducibility and oxidizability. Thus, TDM could be a good referential descriptor for revealing photocatalytic mechanisms in semiconductor photocatalysts and interlayer photoexcitation behavior in layered heterostructures. Hopefully, more strategies via modification of TDMs would be proposed to enhance the visible-light response of a semiconductor without sacrificing its photocatalytic driving force.